Overexpression of Egr1 Transcription Regulator Contributes to Schwann Cell Differentiation Defects in Neural Crest-Specific Adar1 Knockout Mice - Zerad, Lisa; Gacem, Nadjet; Gayda, Fanny; Day, Lucie; Sinigaglia, Ketty; Richard, Laurence; Parisot, Melanie; Cagnard, Nicolas; Mathis, Stephane; Bole-Feysot, Christine; O'Connell, Mary A; Pingault, Veronique; et al. (Cells, 2024)
Adenosine deaminase acting on RNA 1 (ADAR1) is the principal enzyme for the adenosine-to-inosine RNA editing that prevents the aberrant activation of cytosolic nucleic acid sensors by endogenous double stranded RNAs and the activation of interferon-stimulated genes. In mice, the conditional neural crest deletion of Adar1 reduces the survival of melanocytes and alters the differentiation of Schwann cells that fail to myelinate nerve fibers in the peripheral nervous system. These myelination defects are partially rescued upon the concomitant removal of the Mda5 antiviral dsRNA sensor in vitro, suggesting implication of the Mda5/Mavs pathway and downstream effectors in the genesis of Adar1 mutant phenotypes. By analyzing RNA-Seq data from the sciatic nerves of mouse pups after conditional neural crest deletion of Adar1 (Adar1cKO), we here identified the transcription factors deregulated in Adar1cKO mutants compared to the controls. Through Adar1;Mavs and Adar1cKO;Egr1 double-mutant mouse rescue analyses, we then highlighted that the aberrant activation of the Mavs adapter protein and overexpression of the early growth response 1 (EGR1) transcription factor contribute to the Adar1 deletion associated defects in Schwann cell development in vivo. In silico and in vitro gene regulation studies additionally suggested that EGR1 might mediate this inhibitory effect through the aberrant regulation of EGR2-regulated myelin genes. We thus demonstrate the role of the Mda5/Mavs pathway, but also that of the Schwann cell transcription factors in Adar1-associated peripheral myelination defects.
Keywords: Animals; Mice, Knockout; myši knockoutované; ADAR1; Schwannovy buňky; buněčná diferenciace; Mice; MAVS; Neural Crest; myši; myelinová pochva; adenosindeaminasa; differentiation; EGR1; Interferon-Induced Helicase, IFIH1; neural crest; Cell Differentiation; Schwann Cells; zvířata; IFIH1; Adenosine Deaminase; crista neuralis; Schwann cells; Myelin Sheath